Internalization of Religious Moderation Values Through Learning Moral Sufism with Implications for Student Association Ethics - Hilyah Ashoumi; Ludfiah Novi Cahyani H; Muhammad Kris Yuan Hidayatulloh (SCHOOLAR: Social and Literature Study in Education, 2022)
The modern world that brings changes to human life through the digital world causes various impacts, especially in terms of religion and association. Electronic media shortens our view of the world. Through social media we can change or lead opinions that are not in accordance with moderate religious teachings. Through students as role models for the progress of integrity, internalization of religious moderation values. This study aims to determine a.) strategies for internalizing the values ​​of religious moderation in the Akhlak Tasawuf course b.) the form of implementation of religious moderation values ​​in the Sufism morals course c.) the implications of the values ​​of religious moderation in Sufism morals courses at student ethics. This research uses descriptive qualitative research method. The data collection techniques of this research are interviews, observation, and documentation, while the respondents of this research are shown to teachers of the Sufism morals course and PAI students at Kh Abdul Wahab Hasbullah University. The results of this study explain the internalization process of religious moderation values ​​can be developed in the learning of Sufism morals through learning strategies, learning methods, and learning evaluations so that religious moderation values ​​can be useful in the social ethics of students of Kh Abdul Wahab Hasbullah University.